Influence of NPK fertilizer and spacing on growth parameters of onion (Allium cepa L. var. BARI piaz-1) (Research in Agriculture Livestock and Fisheries, 2019)
The productivity of onion crop is poor due to inappropriate management and agronomic practices in Bangladesh. To figure out the effect of NPK fertilizer rate and spacing on growth parameters of onion a field experiment was conducted. The treatments were consisting of N fertilizer (0, 80,120 and 160 kg/ha), P fertilizer (0, 30, 50 and 70 kg/ha), k fertilizer (0, 50, 75 and 100 kg/ha) and three plant spacing viz., 10 cm × 10 cm, 15 cm × 10 cm and 20 cm × 10 cm. The experiment was designed in RCBD with three replications. Analysis of results indicates that the interaction effect of NPK rate and spacing shows significant (P